2021
DOI: 10.1007/s00394-021-02551-x
|View full text |Cite
|
Sign up to set email alerts
|

A1- and A2 beta-casein on health-related outcomes: a scoping review of animal studies

Abstract: Purpose Food-derived bioactive peptides may influence important physiological functions. An important example is beta-casomorphins, which are opioid peptides derived from A1 beta-casein in bovine milk and have been associated to be risk factors for non-communicable diseases in humans. A1 and A2 beta-casein are different with respect to the release of bioactive peptides, in particular BCM-7. However, evidence from human studies is limited and could be complemented with evidence derived from animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 47 publications
0
21
0
2
Order By: Relevance
“…As far as other health outcomes (CVD, diabetes, neurological diseases) are concerned, according to Kuellenberg de Gaudry and colleagues ( 6 ), the certainty of the evidence, according to the GRADE assessment, was judged as very low for most health outcomes considered in clinical trials and epidemiological studies published prior to October 2017. Using the same methodological approach, this was confirmed by Danilowsky and colleagues ( 1 ), for clinical trials and animal studies published prior to 2021 and for animal –based studies published prior to 2020 ( 7 ).…”
Section: Methodsmentioning
confidence: 69%
See 3 more Smart Citations
“…As far as other health outcomes (CVD, diabetes, neurological diseases) are concerned, according to Kuellenberg de Gaudry and colleagues ( 6 ), the certainty of the evidence, according to the GRADE assessment, was judged as very low for most health outcomes considered in clinical trials and epidemiological studies published prior to October 2017. Using the same methodological approach, this was confirmed by Danilowsky and colleagues ( 1 ), for clinical trials and animal studies published prior to 2021 and for animal –based studies published prior to 2020 ( 7 ).…”
Section: Methodsmentioning
confidence: 69%
“…Despite the large range of evidence on the effects of food- derived opioids on delayed intestinal transit, intestinal inflammation, intestinal permeability and an altered microbiome, it is clear that, when analyzing the conclusions of the narrative reviews, considerable variability in evidence exists regarding the effect on non-communicable diseases. The four systematic reviews published between 2017 and 2021 ( 1 , 5 7 ) constitute a tool for interpreting such variability. These reviews were all conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist, with the aim of critically analyzing the existing data from well-controlled human clinical trials and animal studies on the impact of ingestion of A1 β-CN milk and A2 β-CN milk on health-related outcomes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although related reviews have gathered a large amount of scientific evidence, the role of β-casomorphins (BCMs), such as BCM-7, and their physiological functions remain controversial, and more research with improved diagnostic techniques is needed to unequivocally determine their mechanism of action and study their possible health-related impacts [ 22 ]. Recently, other reviews [ 15 , 58 , 59 , 60 ] concluded that human-based published evidence provided moderate certainty for the adverse digestive health effects of A1 β-casein compared with A2 β-casein, but only indications and not conclusive evidence for the relation with other health effects. Globally, the adverse effects of BCM-7 on health have obtained positive results when experimental animal models were used for their study.…”
Section: Implications For Human Health Of Dairy β-Caseins and β-Casom...mentioning
confidence: 99%